Studies Regarding Mechanical Properties Improvement of Aluminum Alloy Type AtSi5Cux and Results Validation by Calculating Precision Indicators. (2016) - Stoicanescu, Maria; Smeada, Mihaela
Abstract: Experimental studies performed in order to improve the specific characteristics of materials used by modern technologies have always represented a stringent demand. The current paper presents the results of the experimental researches performed on aluminum alloys, together with their statistical interpretation and data validation by means of precision indicators. Mechanical vibrations applied to an environment in which aging carries out lead to increasing efficiency of heat treatment due to elastic deformations of the base cell [3, 7] . Thus, a significantly growing hardness is obtained as compared to samples subjected to classical treatment [10, 11] .